Turning point for all nations (Baha'i International Community New YorkUS, 1995)
Defines a role for the UN within the emerging International Order and seeks to find ways of releasing the power of the individual. Makes a call to world leaders.
Statement on the occasion of the 50th anniversary of the United Nations